Improving sweetpotato virus diagnostics - Kreuze, Jan F. (International Potato Center, 2015)
This flyer describes progress made between June 2014 and July 2015 to develop an easily accessible distribution map of all relevant viruses and virus strains infecting sweetpotato throughout SSA as well as appropriate diagnostic methods and protocols to detect them. It provides details about a generic virus detection method developed at CIP called small RNA sequencing and assembly (sRSA) to determine all viruses infecting sweetpotato in SSA: the pan-African sweetpotato Virome; as well as two diagnostic methods for detecting sweetpotato viruses: micro-arrays in a test tube (ClonDiag arrays) and an isothermal amplification method (LAMP).